Usefulness of diffusion tensor imaging in amyotrophic lateral sclerosis: potential biomarker and association with the cognitive profile - Marcelo Chaves; Mariela Bettini; Maria Cecilia Fernandez; Maria Jose Garcia Basalo; Juan Ignacio Rojas; Cristina Besada; Edgardo Cristiano; Angel Golimstok; Marcelo Rugiero (Arquivos de Neuro-Psiquiatria)
ABSTRACT The objective of this preliminary study was to correlate diffusion tensor imaging (DTI) alterations with the cognitive profile of patients with amyotrophic lateral sclerosis (ALS). Methods This was a case-control study conducted from December 1, 2012 to December 1, 2014. Clinical and demographic data were recorded. A neuropsychological test battery adapted to ALS patients was used. An MRI with DTI was performed in all patients and fractional anisotropy (FA) was analyzed in the white matter using the tract based spatial statistics program. Results Twenty-four patients with ALS (15 females, mean age 66.9 + -2.3) and 13 healthy controls (four females, average age 66.9 + - 2) were included. The DTI showed white matter damage in ALS patients vs. healthy controls (p < 0.001). Discussion In our preliminary study the alterations of white matter in DTI were significantly associated with cognitive impairment in patients with ALS.